2019
DOI: 10.1016/j.atherosclerosis.2019.01.011
|View full text |Cite
|
Sign up to set email alerts
|

The novel inflammatory marker GlycA and the prevalence and progression of valvular and thoracic aortic calcification: The Multi-Ethnic Study of Atherosclerosis

Abstract: Background and aims: GlycA is a novel composite biomarker of systemic inflammation reflecting posttranslational glycosylation of acute phase reactants. GlycA has been associated with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…BMI, physical activity, smoking, blood pressure, glucose, cholesterol)–health metrics which are also risk factors for AF [ 18 ]. Higher GlycA levels have been linked with subclinical atherosclerosis [ 30 , 33 , 34 ], incident CVD [ 19 22 ], and with heart failure with preserved ejection fraction [ 23 ]. In a prior MESA study comparing the predictive value of GlycA and other inflammatory biomarkers, GlycA had a significantly predictive value comparable to hsCRP, IL-6, and D-dimer, if not superior, for total death, CVD, chronic inflammatory-related severe hospitalization and death, and total cancer [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…BMI, physical activity, smoking, blood pressure, glucose, cholesterol)–health metrics which are also risk factors for AF [ 18 ]. Higher GlycA levels have been linked with subclinical atherosclerosis [ 30 , 33 , 34 ], incident CVD [ 19 22 ], and with heart failure with preserved ejection fraction [ 23 ]. In a prior MESA study comparing the predictive value of GlycA and other inflammatory biomarkers, GlycA had a significantly predictive value comparable to hsCRP, IL-6, and D-dimer, if not superior, for total death, CVD, chronic inflammatory-related severe hospitalization and death, and total cancer [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…37 Several other studies have shown similar positive associations between GlycA and incident CVD, mortality, and cancer 4 and have shown that the relationship with CVD was stronger for GlycA than that reported for hsCRP 38 and is independent of hsCRP. 39 Despite the aforementioned established association of GlycA with incident CVD events 4 and with subclinical coronary and extra-coronary atherosclerosis, 20,21,40 the relationship of GlycA with subclinical and clinical PAD, specifically, had not been previously established. Although there are some common shared cardiovascular risk factors that promote atherosclerosis across various vascular beds, risk factors are not necessarily overlapping.…”
Section: Discussionmentioning
confidence: 99%
“…Sixth, we performed multiple tests and results may be due to chance; however, findings were consistent with our a priori hypotheses and with other studies that have established a link between GlycA and atherosclerosis. 20,21 Finally, MESA recruitment took place in the early 2000s, which limits the study's generalizability to current day where primary prevention therapies are more prevalent and are more widely used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations